(3GdefgGL aj TYH GdEjeGfs - (3CHh YHO Gddg GdMSjf Hf GdMSf Hf eMeO Hf Mdje GdHNGQj GdLQLGfj GdTGaYj, GdMdjej,J (B403 (3g` s
(3ChdgG (B:s
(3GdKGdK YTQ ef TYH GdEjeGf , hgh aj GdJhcd Ydi Gddg YR hLd s
(3BNQgG (B:s
(3GdKGdK hGdKdGKjf ef GdEjeGf , hgh aj JYOjO fYe Gddg Ld hYR , heG jLH ef TcQgG s
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B235s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B110 s
Keywords: (3GdMOjK h GdeUWdMs